The Influence of Work Motivation on Bawaslu Employees in Bogor Regency on Public Satisfaction - Sholehah, Annisa Zahra; Maruapey, Muhamad Husein; Aprilliyani, Neng Virly (International Journal of Applied Research and Sustainable Sciences, 2024)
Motivation is a factor that encourages a person to carry out certain activities, therefore motivation is often interpreted as a factor driving a person's behavior. Motivated employees tend to work better in carrying out their duties. Public satisfaction with Bawaslu's performance is an important indicator of Bawaslu's success in carrying out its duties. People who are satisfied with Bawaslu's performance tend to have higher trust in the election process. This study uses a quantitative approach with Work Motivation (X) and Public Satisfaction (Y) as variables. It sampled 18 employees and 18 public members using observation, interviews, and questionnaires. The correlation between work motivation and p satisfaction was 0.351, indicating a weak influence. The t-test showed no significant effect (tcount = 1.486, ttable = 1.746). The coefficient of determination (R²) was 0.121, meaning work motivation affects public satisfaction by 12.1%.